Characterisation of endogenous players in fibroblast growth factor‐regulated functions of hypothalamic tanycytes and energy‐balance nuclei. (8th July 2019) - Kaminskas, Benediktas; Goodman, Timothy; Hagan, Andrew; Bellusci, Saverio; Ornitz, David M.; Hajihosseini, Mohammad K.
Abstract: The mammalian hypothalamus regulates key homeostatic and neuroendocrine functions ranging from circadian rhythm and energy balance to growth and reproductive cycles via the hypothalamic‐pituitary and hypothalamic‐thyroid axes. In addition to its neurones, tanycytes are taking centre stage in the short‐ and long‐term augmentation and integration of diverse hypothalamic functions, although the genetic regulators and mediators of their involvement are poorly understood. Exogenous interventions have implicated fibroblast growth factor (FGF) signalling, although the focal point of the action of FGF and any role for putative endogenous players also remains elusive. We carried out a comprehensive high‐resolution screen of FGF signalling pathway mediators and modifiers using a combination of in situ hybridisation, immunolabelling and transgenic reporter mice, aiming to map their spatial distribution in the adult hypothalamus. Our findings suggest that β‐tanycytes are the likely focal point of exogenous and endogenous action of FGF in the third ventricular wall, utilising FGF receptor (FGFR)1 and FGFR2 IIIc isoforms, but not FGFR3. Key IIIc‐activating endogenous ligands include FGF1, 2, 9 and 18, which are expressed by a subset of ependymal and parenchymal cells. In the parenchymal compartment, FGFR1‐3 show divergent patterns, with FGFR1 being predominant in neuronal nuclei and expression of FGFR3 being associated with glial cell function. Intracrine FGFs are also present, suggestive of multiple modes of FGF function. Our findings provide a testable framework for understanding the complex role of FGFs with respect to regulating the metabolic endocrine and neurogenic functions of hypothalamus in vivo.